Transuranic contaminated waste form characterization and data base - Kniazewycz, B. G.; McArthur, W. C. (TERA Corp., Berkeley, CA (USA), 1980)
This volume contains appendices A to F. The properties of transuranium (TRU) radionuclides are described. Immobilization of TRU wastes by bituminization, urea-formaldehyde polymers, and cements is discussed. Research programs at DOE facilities engaged in TRU waste characterization and management studies are described.